Boosting the durability of RuO2 via confinement effect for proton exchange membrane water electrolyzer - Wen-Xing Zheng; Xuan-Xuan Cheng; Ping-Ping Chen; Lin-Lin Wang; Ying Duan; Guo-Jin Feng; Xiao-Ran Wang; Jing-Jing Li; Chao Zhang; Zi-You Yu; Tong-Bu Lu (Nature Communications)
Abstract Ruthenium dioxide has attracted extensive attention as a promising catalyst for oxygen evolution reaction in acid. However, the over-oxidation of RuO2 into soluble H2RuO5 species results in a poor durability, which hinders the practical application of RuO2 in proton exchange membrane water electrolysis. Here, we report a confinement strategy by enriching a high local concentration of in-situ formed H2RuO5 species, which can effectively suppress the RuO2 degradation by shifting the redox equilibrium away from the RuO2 over-oxidation, greatly boosting its durability during acidic oxygen evolution. Therefore, the confined RuO2 catalyst can continuously operate at 10 mA cm–2 for over 400 h with negligible attenuation, and has a 14.8 times higher stability number than the unconfined RuO2 catalyst. An electrolyzer cell using the confined RuO2 catalyst as anode displays a notable durability of 300 h at 500 mA cm–2 and at 60 °C. This work demonstrates a promising design strategy for durable oxygen evolution reaction catalysts in acid via confinement engineering.